Removal of Copper from Aqueous Solutions by Coprecipitation with Hydrated Iron Oxide - Boukhalfa, Chahrazed; Mennour, Ammar; Reinert, Laurence; Dray, Micheline; Duclaux, Laurent (Asian Journal of Chemistry, 2010)
The coprecipitation of Cu(II) ions with hydrated iron oxide in aqueous solution was studied using batch experiments by varying pH, iron and copper concentrations and [Cu(II)]/ [Fe(III)] molar ratio and also in the presence of competing ions. Analytical methods for solids analysis were performed to characterize the interaction of copper with the surface of the hydrous oxide. The uptake of Cu(II) showed typical cationic-type behaviour. The effect of the molar ratio was shown to depend on the copper concentration at high concentrations anomalous behaviour was observed. In the presence of Pb(II) and Zn(II), the Cu(II) removal was slightly decreased, whereas, it was enhanced in the presence of SO42-.